Trophic Interactions of Infant Bifidobacteria and Eubacterium hallii during L-Fucose and Fucosyllactose Degradation - Schwab, Clarissa; Ruscheweyh, Hans-Joachim; Bunesova, Vera; Pham, Van Thanh; Beerenwinkel, Niko; Lacroix, Christophe (Frontiers in Microbiology, 2017)
Fucosyllactoses (2′- or 3′-FL) account for up to 20% of human milk oligosaccharides (HMOs). Infant bifidobacteria, such as Bifidobacterium longum subsp. infantis, utilize the lactose moiety to form lactate and acetate, and metabolize L-fucose to 1,2-propanediol (1,2-PD). Eubacterium hallii is a common member of the adult gut microbiota that can produce butyrate from lactate and acetate, and convert 1,2-PD to propionate. Recently, a Swiss cohort study identified E. hallii as one of the first butyrate producers in the infant gut. However, the global prevalence of E. hallii and its role in utilization of HMO degradation intermediates remains unexplored. Fecal 16S rRNA gene libraries (n = 857) of humans of all age groups from Venezuela, Malawi, Switzerland, and the USA were screened for the occurrence of E. hallii. Single and co-culture experiments of B. longum subsp. infantis and E. hallii were conducted in modified YCFA containing acetate and glucose, L-fucose, or FL. Bifidobacterium spp. (n = 56) of different origin were screened for the ability to metabolize L-fucose. Relative abundance of E. hallii was low (10−5–10−3%) during the first months but increased and reached adult levels (0.01–10%) at 5–10 years of age in all four populations. In single culture, B. longum subsp. infantis grew in the presence of all three carbohydrates while E. hallii was metabolically active only with glucose. In co-culture E. hallii also grew with L-fucose or FL. In co-cultures grown with glucose, acetate, and glucose were consumed and nearly equimolar proportions of formate and butyrate were formed. B. longum subsp. infantis used L-fucose and produced 1,2-PD, acetate and formate in a ratio of 1:1:1, while 1,2-PD was used by E. hallii to form propionate. E. hallii consumed acetate, lactate and 1,2-PD released by B. longum subsp. infantis from FL, and produced butyrate, propionate, and formate. Beside B. longum subsp. infantis, Bifidobacterium breve, and a strain of B. longum subsp. suis were able to utilize L-fucose. This study identified a trophic interaction of infant bifidobacteria and E. hallii during L-fucose degradation, and pointed at E. hallii as a metabolically versatile species that occurs in infants and utilizes intermediates of bifidobacterial HMO fermentation.